Exactly how to sell : the sales guide for non-sales professionals - Jones, Phil M., 1981- (Wiley, 2018)
"Exactly How to Sell is your sales aid, designed to inspire business owners and employees throughout their sales process using tried, tested and proven methods to attract more customers. Phil M Jones writes from experience and explains how to get more customers and keep them all happy, while they are spending more money, more often. Using simple, practical and easy to implement methods in-line with the modern business landscape, Phil will educate and guide you, giving you the confidence you need to develop into the business you want to be"--